2017
DOI: 10.1097/coc.0000000000000133
|View full text |Cite
|
Sign up to set email alerts
|

Late Toxicity and Outcomes in High-risk Prostate Cancer Patients Treated With Hypofractionated IMRT and Long-term Androgen Suppression Treatment

Abstract: Dose escalation and hypofractionated radiation treatment with IMRT treating the prostate and proximal SV concurrently with the pelvic lymph nodes and distal SV and long-term androgen suppression therapy is well tolerated with respect to acute and late toxicity with 5-year actuarial overall survival 86.67%, freedom from biochemical failure 91.38%, and freedom from clinical failure 96.67%. Longer follow-up will provide more information on 10-year survival outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
1
4
1
Order By: Relevance
“…Although total dose to the prostate was lower compared to our PLATIN-1 trial according to former guidelines, the reduced number of side effects in the present study can be explained by the use of modern treatment techniques like IMRT in combination with daily imaging (IGRT). This is in accordance with other studies using IMRT: Pervez et al observed no grade 3/4 late GI toxicity in a group of 60 patients undergoing irradiation of the pelvic nodes and prostate (total dose: 45/68 Gy) in 25 fractions at 5 years follow-up timepoint (18). Similar results were described for GU side effects, however, a direct comparison is difficult due to a lack of detailed data in the majority of other reports and a limited number of feedbacks in our cohort.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although total dose to the prostate was lower compared to our PLATIN-1 trial according to former guidelines, the reduced number of side effects in the present study can be explained by the use of modern treatment techniques like IMRT in combination with daily imaging (IGRT). This is in accordance with other studies using IMRT: Pervez et al observed no grade 3/4 late GI toxicity in a group of 60 patients undergoing irradiation of the pelvic nodes and prostate (total dose: 45/68 Gy) in 25 fractions at 5 years follow-up timepoint (18). Similar results were described for GU side effects, however, a direct comparison is difficult due to a lack of detailed data in the majority of other reports and a limited number of feedbacks in our cohort.…”
Section: Discussionsupporting
confidence: 92%
“…However, one crucial question remains: Is there an oncological benefit for pelvic node irradiation in non-metastatic patients with prostate cancer? While several retrospective and small prospective studies report on promising results (9, 18, 21, 2325), two randomized phase III trials failed to show an improved survival for patients undergoing pelvic irradiation (Table 3): The last update of the GETUG-01 randomized study evaluating 446 men with prostate carcinoma summarized, that pelvic nodes irradiation was not able to improve event-free survival (EFS) or OS after a median follow-up of 11.4 years (11). For the RTOG 9413 cohort including 1,322 patients, an improved PFS was observed for NHT plus WPRT compared with NHT plus prostate-only radiotherapy (PORT) and WPRT and adjuvant hormonal therapy after a median follow-up of 8.8 years.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding cumulative GU toxicity, the results are very different between studies. Compared to ours, the Gliksman study [17] reported a higher rate, the Platin trial [20] , and the Adkison [27] and Di Muzio [32] studies, a similar rate and the POP-RT [14] , CHiRP [29] , Magli [18] , Ekanger [28] , Quon [23] , Niazi [30] , Faria [22] , Pervez [19] and Jorgo [31] studies much lower rates. Our high percentage of cumulative GI toxicity could be explained by a higher EQD2 (49 Gy) to lymph nodes than most other studies, even though, in POP RT - which has an EQD2 to lymph nodes at 50 Gy - only 8.2 % of cumulative late grade 2 GI toxicities were reported [14] .…”
Section: Discussionmentioning
confidence: 41%
“…Many studies have evaluated an SIB approach to deliver elective pelvic nodal irradiation together with moderate hypofractionation to the prostate [14] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] . The consistent conclusion from all the published studies is that it is safe with a very acceptable toxicity profile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation